Traditional and new business models in the banking industry - Jatić Sead; Ilić Milena (Bankarstvo, 2018)
The management of today's financial markets would be impossible without banks as the prime mediators in performing a large number of financial activities. The relationship established between banks and their clients is based on the exchange of financial resources and information, often in the long run, in order to achieve numerous common goals. Over the past few decades, banks have advanced and improved their management in order to offer their clients top services. A large part of their business is founded upon innovations as well as specific strategies that have proven to be more or less successful. The business models that are applied in bank management are various, and by continuous innovation in this field banks strive to secure a significant competitive advantage in the market. Recent years have seen the strong competition in the global market and continuous seeking for the business models that could secure long-term business success to the banks. Innovations have been implemented in every segment of the banking business, and development of business models and strategies is the priority at every level of management in today's banks.